Cover Picture: IR‐ATR Chemical Sensors Based on Planar Silver Halide Waveguides Coated with an Ethylene/Propylene Copolymer for Detection of Multiple Organic Contaminants in Water (Angew. Chem. Int. Ed. 8/2013). Issue 8 (1st February 2013) - Lu, Rui; Sheng, Guoping; Li, Wenwei; Yu, Hanqing; Raichlin, Yosef; Katzir, Abraham; Mizaikoff, Boris
<x xml:space="preserve">Abstract</x> Rapidly responding in situ analysis methods, such as mid‐infrared optochemical sensors utilizing evanescent field absorption techniques, may inherently provide qualitative and quantitative information on multiple volatile organic contaminants in water. In their Communication on page 2265 ff., B. Mizaikoff et al. describe a planar infrared attenuated total reflection (IR‐ATR) fiberoptic sensor that was coated with an ethylene/propylene copolymer. Such a system may be used for continuous monitoring of the water quality.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>